Molecular Insulin Actions Are Sexually Dimorphic in Lipid Metabolism - Ortiz-Huidobro, Rosa Isela; Velasco, Myrian; Larqué, Carlos; Escalona, Rene; Hiriart, Marcia (Frontiers in Endocrinology, 2021)
The increment in energy-dense food and low physical activity has contributed to the current obesity pandemic, which is more prevalent in women than men. Insulin is an anabolic hormone that regulates the storage of lipids, carbohydrates, and proteins in adipose tissue, liver, and muscle. During obesity, nutrient storage capacity is dysregulated due to reduced insulin action in its target organs, producing insulin resistance, an early marker of metabolic dysfunction. Insulin resistance in adipose tissue is central in metabolic diseases due to the critical role that this tissue plays in energy homeostasis. Considering that the study of sexual dimorphism has taken great relevance in recent years and the ample clinical and epidemiological evidence of its influence on the establishment and progression of metabolic diseases, this review is focused on the role of sexual dimorphism on the molecular mechanism of insulin actions and its relationship with the physiology and pathophysiology of adipose tissue. Sexual dimorphism is a critical factor in designing sex-targeted therapeutic strategies and public health policies on obesity and diabetes.